Lifestyle InterVention IN Gestational diabetes (LIVING) in India, Bangladesh and Sri Lanka: protocol for process evaluation of a randomised controlled trial. Issue 12 (13th December 2020) - Shanthosh, Janani; Kapoor, Deksha; Josyula, Lakshmi K; Patel, Anushka; Gupta, Yashdeep; Tandon, Nikhil; Jan, Stephen; Teede, Helena J; Desai, Ankush; Joshi, Rohina; Praveen, Devarsetty
Abstract : Introduction: The development of type 2 diabetes mellitus disproportionately affects South Asian women with prior gestational diabetes mellitus (GDM). The Lifestyle InterVention IN Gestational diabetes (LIVING) Study is a randomised controlled trial of a low-intensity lifestyle modification programme tailored to women with previous GDM, in India, Bangladesh and Sri Lanka, aimed at preventing diabetes/pre-diabetes. The aim of this process evaluation is to understand what worked, and why, during the LIVING intervention implementation, and to provide additional data that will assist in the interpretation of the LIVING Study results. The findings will also inform future scale-up efforts if the intervention is found to be effective. Methods and analysis: The Reach Effectiveness Adoption Implementation Maintenance (RE-AIM) methodological approach informed the evaluation framework. Michie's Behaviour Change Theory and Normalisation Process Theory were used to guide the design of our qualitative evaluation tools within the overall RE-AIM evaluation framework. Mixed methods including qualitative interviews, focus groups and quantitative analyses will be used to evaluate the intervention from the perspectives of the women receiving the intervention, facilitators, site investigators and project management staff. The evaluation will use evaluation datasets, administratively collected process data accessed during monitoring visits, check lists and logs, quantitative participant evaluation surveys, semistructured interviews and focus group discussions. Interview participants will be recruited using maximum variation purposive sampling. We will undertake thematic analysis of all qualitative data, conducted contemporaneously with data collection until thematic saturation has been achieved. To triangulate data, the analysis team will engage in constant iterative comparison among data from various stakeholders. Ethics and dissemination: Ethics approval has been obtained from the respective human research ethics committees of the All India Institute of Medical Sciences, New Delhi, India; University of Sydney, New South Wales, Australia; and site-specific approval at each local site in the three countries: India, Bangladesh and Sri Lanka. This includes approvals from the Institutional Ethics Committee at King Edwards Memorial Hospital, Maharaja Agrasen Hospital, Centre for Disease Control New Delhi, Goa Medical College, Jawaharlal Institute of Postgraduate Medical Education and Research, Madras Diabetes Research Foundation, Christian Medical College Vellore, Fernandez Hospital Foundation, Castle Street Hospital for Women, University of Kelaniya, Topiwala National Medical College and BYL Nair Charitable Hospital, Birdem General Hospital and the International Centre for Diarrhoeal Disease Research. Findings will be documented in academic publications, presentations at scientific meetings and stakeholder workshops. Trial registration numbers: Clinical Trials Registry of India (CTRI/2017/06/008744); Sri Lanka Clinical Trials Registry (SLCTR/2017/001) and ClinicalTrials.gov Registry (NCT03305939 ); Pre-results.